PENGEMBANGAN PEMBELAJARAN MATEMATIKA DENGAN MEMASUKKAN NILAI-NILAI ISLAMI PADA MATERI BILANGAN BULAT - Lisanul Uswah Sadieda; Ainur (Universitas Islam Malang, 2015)
Mathematics is a basic science that not only teaches numbers, but in the learning process also trains logical, analytical, systematic and critical thinking ability that useful to whet intellectual. Mathematics can also be a means of instilling Islamic values to students early on to whet their spiritual intelligence in amid the rapid development of the times which leaves the negative impact that is moral decadence. Therefore the aim of this study was to determine how the validity, practicality and effectiveness of the mathematics learning sets by entering the Islamic values in the subject matter of integers at fourth grade MI Mambaul Ulum Terik Krian Sidoarjo. This type of research is the development research using 4-D models of Thiagarajan which consists of four stages which are limited to the stage of develop (development). The results showed that the learning sets are valid, practical and effective. The validity of RPP at 3.93, the validity of textbooks at 3.65, and the validity of LKS at 3.73. The learning sets meets the criteria of practical learning with an average of 3. While the effectiveness criteria are met due to the activity of teachers at 3.36, active student activities as much as 63.33%, mastery learning students by 77.78%, and the positive response of students at 80.56 %.